“I Can Hear the Grass Grow”: The Anatomy of Distributive Changes in Argentina - Walter Sosa Escudero; Sergio Petralia (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2010)
We present a detailed description of the drastic changes in many aspects of the distribution of income in Argentina, complementing a recent study by Gasparini and Cruces (2009), who focus mostly on inequality. We use modern descriptive tools to provide a complete map of the changes in many aspects of the distribution of income, and stress the fact that other key measures changes dramatically along inequality. In particular, we focus on documenting the changes in inequality along those of poverty and the size of the middle class.
Keywords: C15; D31; I21; J23; J31; 330; Einkommensverteilung; Gini-Koeffizient; Argentinien